The spiritual dimension of man: an Islamic psycho-spiritual study - Abdul Razak, Mohd Abbas; Haneef, Sayed Sikandar Shah (Bangladesh Institute of Islamic Thought, 2017)
The discussion on the mind and body continues to be debated by philosophers and psychologists. Ever since the Renaissance, Western scholars have shifted their research on the man from a religious to a scientific one. They argued that spirituality cannot be scrutinized using science and scientific tools. Yet, they are not any closer to finding a comprehensive solution to many of man’s psychological problems. In realizing that man’s spiritual dimension is an area avoided by Western mainstream psychology, this study analyzes some aspects of the soul entity and its varied manifestations from an Islamic perspective. Through a review of related literature and documentary analysis, this study highlights the spiritual dimension of man as understood by Muslims scholars and psychologists.